Cryopreserved neonatal hepatocytes may be a source for transplantation: Evaluation of functionality toward clinical use. Issue 3 (23rd February 2018) - Lee, Charlotte A.; Dhawan, Anil; Iansante, Valeria; Lehec, Sharon; Khorsandi, Shirin E.; Filippi, Celine; Walker, Simon; Fernandez‐Dacosta, Raquel; Heaton, Nigel; Bansal, Sanjay; Mitry, Ragai R.; Fitzpatrick, Emer
Abstract : Neonatal livers are a potential source of good‐quality hepatocytes for clinical transplantation. We compared viability and function of neonatal hepatocytes (NHs) and adult hepatocytes (AHs) and report their clinical use both intraportally and in alginate microbeads. Following isolation from donor livers, hepatocyte function was assessed using albumin, alpha‐1‐antitrypsin, and factor VII. Metabolic function was investigated by measuring resorufin conjugation, ammonia metabolism, uridine diphosphate glucuronosyltransferase enzyme activity, and cytochrome P450 (CYP) function following induction. Activation of the instant blood‐mediated inflammatory reaction by NHs and AHs was investigated using an in vitro blood perfusion model, and tissue factor expression was analyzed using real‐time polymerase chain reaction (RT‐PCR). Clinical hepatocyte transplantation (HT) was undertaken using standard protocols. Hepatocytes were isolated from 14 neonatal livers, with an average viability of 89.4% ± 1.8% (mean ± standard error of the mean) and average yield of 9.3 × 10 6 ± 2.0 × 10 6 cells/g. Hepatocytes were isolated from 14 adult livers with an average viability of 78.6% ± 2.4% and yield 2.2 × 10 6 ± 0.5 × 10 5 cells/g. NHs had significantly higher viability after cryopreservation than AHs, with better attachment efficiency and less plasma membrane leakage. There were no differences in albumin, alpha‐1‐antitrypsin, and factor VII synthesis between NHs and AHs ( P > 0.05). Neonatal cells had inducible phase 1 enzymes as assessed by CYP function and functional phase 2 enzymes, in which activity was comparable to AHs. In an in vitro blood perfusion model, AHs elicited increased thrombus formation with a greater consumption of platelets and white cells compared with NHs (28.3 × 10 9 versus 118.7 × 10 9 and 3.3 × 10 9 versus 6.6 × 10 9 ; P < 0.01). Intraportal transplantation and intraperitoneal transplantation of alginate encapsulated hepatocytes was safe, and preliminary data suggest the cells may activate the immune response to a lesser degree than adult cells. In conclusion, we have shown NHs have excellent cell viability, function, and drug metabolism making them a suitable alternative source for clinical HT. Liver Transplantation 24 394–406 2018 AASLD.